(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2024)
In this study, a substrate integrated waveguide dielectric resonator antenna excited by an L-slot is proposed, and the design is operated within the frequency range of 24.25 to 29.5 GHz bandwidth for 5G-NR applications. Rogers 5880 is used as a substrate with a permittivity of 2.2; in contrast, the dielectric resonator antenna has a permittivity of 10. The antenna demonstrates a simulated impedance bandwidth of 25.2 to 30.5 GHz, and a high gain of 8.7 dBi is observed due to the excitation of the DRA higher-order TE113 mode, whereas the design exhibits over 98% radiation efficiency, attributed to minimal copper losses at resonant frequencies. These results highlight the antenna’s suitability for broadband, high-efficiency, high-gain applications in the millimeter-wave 5G-NR frequency bands.